Public Works Tax Deduction: Bottlenecks and Improvement Proposal - Salinas Rivas, Sergio Fernando Pedro (2015)
This article describes and analyses the present conditions of the application of the Public Work Tax Deduction (PWTD) mechanism, identifying six main obstacles that difficult on a appreciable way his concrete implementation or the rate of it.For this purpose, this study has identify and analyze the 30 main highlights that conform the critical path of PWTD process, determining the actual times for his performance and comparing them with the legal times established on the PWTD actual law, and so with the optimal times reasonably according with the experience on the public management of similar work projects.